(untitled) (Agricultural Engineering, 2022)
The objective of the paper is to analyse changes in the new farm tractor market in Poland and the annual income of farmers’ households generated in the same period. The studies covered the period from 2010 to 2020. The new farm tractors market was analysed with reference to the number of sold tractors, which was measured by the number of registrations. The paper considers quarterly seasonality of sale along with demand for selected producers and engine-power categories of new farm tractors sold in Poland. By “new tractors” the authors mean those registered for the first time in Poland and manufactured in the same or the preceding year. In 2010-2020, there were over 148,000 new farm tractors registered in Poland. The highest number of tractors sold was recorded in 2012, the lowest in 2016. Tractors from Western Europe, USA, and Japan predominate on the Polish market. Among new vehicles, the highest number registered in the investigated period constituted New Holland (23,780) tractors, followed by John Deere (19,453), Zetor (16,398), Deutz-Fahr (10,508), and Kubota (7,674). The total share of these producers in 2010-2020 amounted to approx. 58%. With regard to the engine-power categories in the analysed period, tractors with power of 37-73 kW and 74-132 kW (33.85%) constituted the largest proportion (49.07%). An increased interest in tractors with power below 36 kW was also observed from 2016 to 2020. Such vehicles accounted for 10% of all registrations. The general trend related to the volume of average annual income is not consistent with the trend of purchasing new farm tractors, while the highest number of registrations was recorded during the period in which inflation rates reached their highest values.